Análise morfológica da cabeça da mandíbula por tomografia computadorizada de feixe cônico em indivíduos jovens com ou sem Síndrome de Down - Pereira, Alexandre Miranda (2013)
The Tempormandibular joint (TMJ) is considered to be the most complex of the human body. It is classified as synovial, and then presents capsule and articular disc, membrane, synovial fluid and ligaments. Particularly, TMJ is a form of connection between the mandibular condyle (face) and temporal bone (skull), which generates a mechanically stable joint component. There are currently few studies concerning the study of TMJ in patients with Down syndrome (DS) (trisomy 21). The aim of this study is to morphologically analyze the mandibular condyle by means of Cone Beam Computed Tomography (CBCT) in young individuals with or without SD. After ethical approval, 23 patients were allocated (male or female and aged between 18 and 20 years), 10 patients with SD (study group) and 13 young people without such Syndrome. Morphological analysis (size and shape in three-dimensional approach) of the mandibular condyle was bilaterally determined by i-CAT Cone Beam Tomography (cone beam ®) imaging detector. The classification of the shape and size of the mandibular condyle was obtained by visualizations of coronal and sagittal planes, as well as by mandibular points. The statistical analyzes included determining the frequency of occurrence for the parameters considered above, with the use of Fisher's exact test, as well as estimating the average continuous quantitative variables by Student's t test. The average size of the mandibular condyle in the control group, left and right sides was 9.71 mm and 9.58 mm in sagittal analysis, while in the Group with Down syndrome was 10.15 mm and 9.97 mm. In coronal analysis the average size of the mandibular condyle, left and right sides, in the control group was 15.59 mm and 15.49 mm, while in the group with Down syndrome was 14.53 mm and 15.12 mm. Cone Beam Computed Tomography (CBCT) is a excellence imaging method employing reduced amount of radiation in a single measurement, low cost and versatility for image reconstruction. In the morphological analysis of the mandibular condyle of young people with or without Down syndrome detected by Cone Beam CT by sagittal and coronal visualizations, there were no significant changes of shape (round and straight) nor size (distance between the extreme anteroposterior and mediolateral mandibular points) comparing both groups. It is suggested that the continued growth potential of the mandibular condyle by temporomandibular joint cartilage remodeling can justify the results. Using tomographic additional incidences associated with a larger sample size could definitively corroborate the findings of this study.